2017
DOI: 10.1007/s00221-017-4976-6
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous reflex modulation during obstacle avoidance under conditions of normal and degraded visual input

Abstract: The nervous system integrates visual input regarding obstacles with limb-based sensory feedback to allow an individual to safely negotiate the environment. This latter source can include cutaneous information from the foot, particularly in the event that limb trajectory is not sufficient and there is an unintended collision with the object. However, it is not clear the extent to which cutaneous reflexes are modified based on visual input. In this study, we first determined if phase-dependent modulation of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…similarly, a study by chen et al [14] revealed postural sway in the mediolateral direction when texting and crossing an obstacle. in addition, the limited visual feedback triggered greater facilitation of cutaneous reflex activation of the biceps femoris, which is responsible for greater knee flexion to avoid the obstacle [39]. This showed evidence of movement adaptation to perform the tasks successfully.…”
Section: Confronting Obstacle Challengementioning
confidence: 85%
“…similarly, a study by chen et al [14] revealed postural sway in the mediolateral direction when texting and crossing an obstacle. in addition, the limited visual feedback triggered greater facilitation of cutaneous reflex activation of the biceps femoris, which is responsible for greater knee flexion to avoid the obstacle [39]. This showed evidence of movement adaptation to perform the tasks successfully.…”
Section: Confronting Obstacle Challengementioning
confidence: 85%
“…The reflexes evoked by sural stimulation are modulated with a presumably functional purpose by the locomotor activity as well (see 62 ). A modulation of a cutaneous reflex from the skin of the foot dorsum (by stimulation of the superficial peroneal nerve), dependent on the task of avoiding an obstacle, 63 occurs during locomotion and is stronger when vision is experimentally degraded. A most remarkable synthesis of the effects of cutaneous input from discrete regions of the foot during walking can be found in Pearcey and Zehr.…”
Section: Cutaneous Input and Gaitmentioning
confidence: 99%